An EP2 Agonist Facilitates NMDA-Induced Outward Currents and Inhibits Dendritic Beading through Activation of BK Channels in Mouse Cortical Neurons - Yoshinori Hayashi; Saori Morinaga; Xia Liu; Jing Zhang; Zhou Wu; Takeshi Yokoyama; Hiroshi Nakanishi (Mediators of Inflammation)
Prostaglandin E2 (PGE2), a major metabolite of arachidonic acid produced by cyclooxygenase pathways, exerts its bioactive responses by activating four E-prostanoid receptor subtypes, EP1, EP2, EP3, and EP4. PGE2 enables modulating N-methyl-D-aspartate (NMDA) receptor-mediated responses. However, the effect of E-prostanoid receptor agonists on large-conductance Ca2+-activated K+ (BK) channels, which are functionally coupled with NMDA receptors, remains unclear. Here, we showed that EP2 receptor-mediated signaling pathways increased NMDA-induced outward currents (INMDA-OUT), which are associated with the BK channel activation. Patch-clamp recordings from the acutely dissociated mouse cortical neurons revealed that an EP2 receptor agonist activated INMDA-OUT, whereas an EP3 receptor agonist reduced it. Agonists of EP1 or EP4 receptors showed no significant effects on INMDA-OUT. A direct perfusion of 3,5′-cyclic adenosine monophosphate (cAMP) through the patch pipette facilitated INMDA-OUT, which was abolished by the presence of protein kinase A (PKA) inhibitor. Furthermore, facilitation of INMDA-OUT caused by an EP2 receptor agonist was significantly suppressed by PKA inhibitor. Finally, the activation of BK channels through EP2 receptors facilitated the recovery phase of NMDA-induced dendritic beading in the primary cultured cortical neurons. These results suggest that a direct activation of BK channels by EP2 receptor-mediated signaling pathways plays neuroprotective roles in cortical neurons.